Child Labour and Multidimensional Deprivation: Evidence from Nizamabad District - Prameela , Y; Reddy, K.Ravinder (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Child labour remains a serious socio-economic and developmental challenge in India, particularly in economically backward regions. This paper examines the multidimensional deprivation experienced by working children in Nizamabad District using a composite index approach. Primary data were collected from 313 working children engaged in various sector activities. Standardised indices were constructed for health status, educational status, work burden, leisure availability, and psychological well-being, which were aggregated into an Overall Well-being Index (OWI). The results reveal low to moderate levels of well-being across all dimensions, indicating that child labour adversely affects children’s holistic development. The study highlights the need for integrated policy interventions focusing on education, health, reduced work intensity, leisure, and psychological support.